ANALISIS PERBANDINGAN KINERJA VIRTUALISASI SERVER MENGGUNAKAN PROXMOX DAN VMWARE ESXI (STUDI KASUS : VIRTUALISASI SERVER UNTUK PENGGUNAAN MOODLE) - Akbar Borneo Dammara; Ipam Fuaddina Adam; Mega Pranata (Jurnal Teknoinfo, 2023)
Server virtualization is a technology that utilizes several computers into one as a server service, so that in its use it does not use too many physical computers. Because a system that uses a virtual system where using a computer alone can provide a service to many computers at once with the virtualization system, research conducted by researchers focused on the performance of virtual servers on server software in Proxmox and VMWare ESXi software with virtual machines that access the Moodle system. However, an efficient system needs to use good software so that it facilitates research in designing the system. The test scheme carried out by the author in this study is testing the CPU load, Memory Speed, and Moodle Benchmark Plugin on the Virtual Machine which contains Moodle in Proxmox and VMWare ESXi as a virtual server used in Moodle e-Learning as well as benchmarking on moodle itself. This study aims to analyze the performance of virtual server service provider software in the online learning management system to find out its advantages and disadvantages so as to make it easier for educational institutions to choose virtual server provider software, especially in Proxmox and VMWare ESXi software.